1987
DOI: 10.1111/j.1755-3768.1987.tb02583.x
|View full text |Cite
|
Sign up to set email alerts
|

Visual field prognosis in advanced glaucoma

Abstract: 79 eyes in 71 patients with advanced glaucomatous damage (loss of at least half the visual field) have been followed for 5-18 years. At the first visit 42 eyes had an intraocular pressure of 40 mmHg or higher. During the followup the visual field defect was stable in 23 eyes (29%) and progressed in 56 eyes (71%). Deterioration of the field was not dependent on the initial degree of defect. Central vision was lost in 27 eyes, and 16 eyes became amaurotic. The visual field was unchanged in 36% of the operated ey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(23 citation statements)
references
References 7 publications
1
21
0
1
Order By: Relevance
“…Odberg18 noted in a cohort of patients with advanced glaucoma 70% of the affected eyes had progressed after a mean of 7.6 years despite treatment. Wilson et al 20 found that initial field loss was the strongest determinant of the rate of further field loss.…”
Section: Advanced Glaucoma At Presentation—a Risk Factor For Blindnessmentioning
confidence: 96%
See 1 more Smart Citation
“…Odberg18 noted in a cohort of patients with advanced glaucoma 70% of the affected eyes had progressed after a mean of 7.6 years despite treatment. Wilson et al 20 found that initial field loss was the strongest determinant of the rate of further field loss.…”
Section: Advanced Glaucoma At Presentation—a Risk Factor For Blindnessmentioning
confidence: 96%
“…Odberg18 in his retrospective cohort of patients with advanced glaucoma noted that lower IOPs were generally achieved with surgical intervention.…”
Section: Evidence For Better Outcomes For Surgical or Medical Treatmentsmentioning
confidence: 99%
“…3,5,[7][8][9] Reduction in intraocular pressure is the only treatable risk factor for glaucoma and may be achieved by either medical or surgical intervention. NICE guidelines have recommended that patients who present with advanced glaucoma should be offered primary glaucoma surgery.…”
Section: Introductionmentioning
confidence: 99%
“…These reports have implied that approximately 5-15% of patients with moderate or advanced glaucomatous damage usually progressed with a mean IOP of between 13 and 18 mmHg over 5 years. 16,17,19,[21][22][23][24][25][26] Several studies, however, have indicated a further benefi t in advanced glaucoma patients of IOPs as low as 12-13 mmHg. 19,23,25 In contrast, generally, IOPs above 18 mmHg have led to greater incidences of progressive glaucomatous damage.…”
Section: Discussionmentioning
confidence: 99%
“…16,17,19,[21][22][23][24][25][26] Several studies, however, have indicated a further benefi t in advanced glaucoma patients of IOPs as low as 12-13 mmHg. 19,23,25 In contrast, generally, IOPs above 18 mmHg have led to greater incidences of progressive glaucomatous damage. For example, in several reports, patients with slightly higher mean IOPs (19)(20)(21) progressed in approximately 50-67% of cases, and in almost 100% of patients, progression occurred with IOPs ≥22 mmHg.…”
Section: Discussionmentioning
confidence: 99%